Teaching Beyond the Classroom: The Bhagavad Gita as My Signature Pedagogy - Dotel, Sudan Prasad (Literary Studies, 2026)
This article explores the concept of signature pedagogy and highlights the author's distinctive teaching approach that centers around the teachings of the Bhagavad Gita, a treasure chest of knowledge. It describes how the author discovered the transformative power of the Bhagavad Gita and its ability to inspire and motivate students. This study employs a qualitative, narrative inquiry approach to explore the integration of the Bhagavad Gita into the author’s signature pedagogy. The methodology is grounded in autoethnography, which combines personal reflection and professional practice to provide an in-depth understanding of how philosophical teachings can shape educational experiences (Ellis et al.). By incorporating verses and insights from the Bhagavad Gita into teaching, the author creates an environment that nurtures intellectual growth, emotional well-being, and spiritual awareness. To further elucidate, the article includes a narrative and a letter as data, illustrating how the author's signature pedagogy influenced and supported a troubled student struggling with addiction in overcoming his challenges and transforming his life.